A Common Fixed Point Theorem for Generalised F-Kannan Mapping in Metric Space with Applications. (17th April 2021) - Wangwe, Lucas; Kumar, Santosh
Abstract : This paper is aimed at proving a common fixed point theorem for F -Kannan mappings in metric spaces with an application to integral equations. The main result of the paper will extend and generalise the recent existing fixed point results in the literature. We also provided illustrative examples and some applications to integral equation, nonlinear fractional differential equation, and ordinary differential equation for damped forced oscillations to support the results.